Phytochemical screening for antibacterial activity of potential Malaysian medicinal plants - Jamal, Parveen; Abdul Karim, Mohamed Ismail; Abdullah, Erlina; Ahmad Raus, Raha; Hashim, Yumi Zuhanis Has-Yun (Academic Journals, 2011)
Plants have been identified for its valuable properties from traditional medicine since thousands of years ago. The huge diversity of the Malaysian flora that has chemical diversity is one of the vital factors that make natural products outstanding candidates for any screening practice. In this research, the leaves of five local plants which are Centella asiatica (‘pegaga’), Ficus deltoidea (‘mas cotek’), Orthosiphon aristatus (‘misai kucing’), Polygonum minus (‘kesum’), and Psidium guajava (‘jambu batu’) were evaluated for their antibacterial properties towards the growth of Bacillus subtilis and Escherichia coli . Methanol, ethanol, and distilled water were used as solvent to extract the plant samples. Preliminary screening showed that ethanol extract of P.guajava had resulted in the highest zone of inhibition against Bacillus subtilis growth.